An anti-biofilm material: polysaccharides prevent the precipitation reaction of silver ions and chloride ions and lead to the synthesis of nano silver chloride. (12th May 2021) - Li, Kun; Liu, Zhaoxi; Liu, Xiaoyu; Wang, Lei; Zhao, Jiayu; Zhang, Xunlian; Kong, Yun; Chen, Min
Abstract: The formation of biofilm is one of the causes of bacterial pathogenicity and drug resistance. Recent studies have reported a variety of anti-biofilm materials and achieved good results. However, it is still very important to develop some materials with wider application scenarios or higher biofilm resistance. In this study, a new method to rapidly synthesize nano silver chloride with anti-biofilm activity is proposed. It is a generalizable method in which bacterial extracellular polysaccharides are used to adsorb silver ions, thereby inhibiting the formation of white large-size silver chloride precipitates, and then ultraviolet light is used to induce the synthesis of small-sized nano silver chloride. A variety of polysaccharides can be utilized in the synthesis of nano silver chloride particles. The generated complex was characterized by XRD, UV–vis, EDX, FTIR and TEM methods. Further, the novel complex was found to show highly effective anti-biofilm and bactericidal activity within the biosafety concentration. In view of the high stability of nano sliver chloride, we propose that the novel nano material has the potential as a long-term antibacterial material.